Lugar de envelhecer: narrativas de idosos - Lopes, Janete da Silva (2014)
The House (Casa) has several signs and meanings that pervade our imaginary upon which we have little conscience. Naturalized and reproduced in our culture, all the symbolic richness from this place is devoid of institutionalized persons. This work s inquiries refer to how we socially devise this place denominated House (Casa) and which is its importance for the elderly people. Starting from social care policies we raise the following issues: what this public policies can offer to elder people in terms of reception? And how to overcome the historic and excluding institutionalization of old-aging, enabling alternative ways of housing and reception for elder people? Our hypothesis is that institutions can offer better life conditions cultivating the characteristics of this ancient place which is the House. This way, the anthropologic exercise proposed by this work used Oral History as its main research method. Diving into the collaboration method, we proposed an involving concept where active subjects -interviewees and interviewer- join together aiming to produce a result that demands connivance (Meihy & Ribeiro: 2011). Our collaborators are people between 61 and 86 years old living on the Programa Vila Dignidade (Dignity Village Program) implemented on the Itapeva municipality, interior of São Paulo state. They reported their stories being the House the key issue. The research highlighted the necessity of extending the concepts and characterizations for the conception of new models of institutional reception, being these considerated as a privileged place for relationship, companionship and transmission of sociocultural values; the House par excellence. Looking closer to the Programa Vila Dignidade some obstacles appeared on its consolidation as a public policy. The first one of them refers to the confusion and strangeness generated and perpetuated by the social care professionals that sometimes reduce it to housing policy refusing possible interfaces with social care policies. The second one refers to closed connections made between this policies: they were badly joint without consensus between its operators, without any foster of a consolidation for a socio-assistencial service to be offered in this Program, neither was previewed the destination of state resources for the financing costs of the actions to be developed, financially burdening the related municipalities. Despite the mentioned limitations, the work carried out revealed the importance of proposals as this one for the construction of new possibilities of old-age living